Broadband Microstrip Antennas. - Kumar, Girish (Artech House, 2002)
A guide to broadband microstrip antennas, offering information on choosing and designing the optimum broadband microstrip antenna configurations for your applications. There are explanations of the various configurations, along with simple design equations.